Wave tank skala laboratorium dengan pembuat gelombang model flap - Murdianto, Deny; Fadilah, Ahmad Nur; Santoso, Hadi; Waluyo, Marhadi Budi (TURBO [Tulisan Riset Berbasis Online], 2024)
One of the first steps in order to utilize ocean waves as electrical energy is to create a medium that can be a means of observing wave characteristics. In this research, a laboratory-scale flap model wave tank was designed. Wave tanks can minimize the use of time and cost in the development of technology that uses ocean waves as a source of energy. The purpose of this research is to design a wave tank with a flap model wave maker, and determine the length and height of the waves produced. This laboratory scale flap model wave tank has a size of 150 cm x 35 cm x 35 cm and uses an electric motor with a power of 200 Watts. The wave tank can work with 22 Watts of electric power and an electric motor rotation of 120 rpm. The maximum height of the waves generated from the laboratory-scale flap model wave tank is 4 cm, while the maximum measured wavelength is 36 cm with a volume of 15% water from the full capacity of the tank.